"Connected leader : creating agile organizations for people, performence and profit" - "Gobillot, Emmanuel" (London, 2007)
What if management thinking to date has been to directed at the wrong problem? What if leadership literature s focus on formal authority and organizational structures has been at the expense of the Real Organisation -the powerful network of informal relationships that doesn t appear on any organizational chart? What then? The result of 150 years of leadership thinking is simple Leaders always eventually fail. In today s context, formal hierachies are no longer effective. Only the real organization, with its cross-cutting networks, is agile enough to respond to the people economy (the new context brought about by mass consumer and employee emancipation). Taking a 21st -Century approach to leadership theory, Emmanuel Gobillot (a senior director at Hay Group) argues that modern leaders need to engage with employees and customers in order to improve performance and profit. Relationships based on trust and meaningful dialogue provide benefits for the organization, employees and customers. The Connected Leader offers both a theoretical background and practical examples for evaluation of leadership skills. Diagnostic tools based on the author s own extensive work in this field provide a unique opportunity for the reader to put theory into practice. What can two singles looking for love on the internet tell you about what your customers wants? Why does it take an anarchist golfer to show you how to meet your customer s needs? What does an 8-year -old nail-varnish-loving girl know about motivating people? Drawing on a varied cast of characters, The Connected Leader shows how our traditional views of organizations limit out ability to deliver results. For leaders this carries an important lesson many of the old leadership recipes are outdated. The connected Leader sounds a passionate wake-up call to leaders everywhere - in politics, business and public service the formal organisation is a myth for success, and leaders must look to the networks of relationships that make up real organisations.
Keywords: Leadership